Asuhan Keperawatan Komunitas pada Masyarakat dengan Hipertensi di Kelurahan Boneoge - Bayu Eka Kurniawan; Agung Viliano (LPPM Universitas Widya Nusantara, 2025)
The community is a social unit that shares common values, norms, habits, and identities, and may be formed based on geographical areas such as villages, cities, or specific neighborhoods. This activity aims to describe the implementation of community nursing care in RT 01 RW 01, Boneoge Village, Banawa District, Donggala Regency. The implementation of health education showed an increase in community knowledge about hypertension, indicating high enthusiasm toward the educational activities conducted by the students. Hypertension education improved community understanding of the signs, symptoms, and preventive measures through balanced diet management and healthy lifestyle practices.